2022
DOI: 10.1007/s10620-022-07727-x
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Functional Gastrointestinal Disorders in Celiac Patients with Persistent Symptoms on a Gluten-Free Diet: A 20-Year Follow-Up Study

Abstract: Background Ongoing symptoms in treated celiac disease (CD) are frequent and are commonly thought of as being due to infractions to a gluten-free diet (GFD) or complications. Aims To study the etiology and natural history of clinically relevant events (CREs) throughout follow-up and identify predictors thereof to guide follow-up. Methods CREs (symptoms/signs requiring diagnostic/therapeutic interventions) occurring in celiac patients between January-2000 and May-2021 were retrospectively collected between June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This aspect is even more important if we consider that modalities for the follow-up of adult patients with CD are not standardised. Follow-up duodenal biopsy is usually not offered routinely to all patients at most centres and the decision on whether or not to repeat a duodenal biopsy is usually taken on a clinical basis, particularly when there is persistence of symptoms despite adherence to a GFD 1–3 10 39 40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect is even more important if we consider that modalities for the follow-up of adult patients with CD are not standardised. Follow-up duodenal biopsy is usually not offered routinely to all patients at most centres and the decision on whether or not to repeat a duodenal biopsy is usually taken on a clinical basis, particularly when there is persistence of symptoms despite adherence to a GFD 1–3 10 39 40…”
Section: Discussionmentioning
confidence: 99%
“…Identification of potential clinical targets in the follow-up of patients with CD is a crucial requirement for clinicians. Based on our results, this includes implementing strategies for obtaining and maintaining over time strict adherence to a GFD,9 control of persistent symptoms despite a GFD11 35 40 and obtaining deep mucosal healing. A substantial degree of overlap between these aspects is likely to exist.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, dietary transgressions are an essential bias in interpreting the clinical course of these patients [ 12 , 16 , 138 ]. An associated pathology is the actual cause of the ongoing symptoms: microscopic colitis [ 147 , 148 , 149 , 150 ], SIBO [ 151 , 152 , 153 , 154 ], malabsorption of simple carbohydrates (e.g., lactose, fructose, or sorbitol) [ 155 , 156 , 157 ], and others such as reflux dysmotility [ 135 ], PEI [ 158 , 159 ], idiopathic bile salt malabsorption [ 160 , 161 , 162 ], Crohn’s disease, [ 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ], and other functional digestive disorders, including irritable bowel syndrome [ 174 , 175 , 176 ]. In such patients, it is obvious that the nature of the symptoms is due to a different cause that overlaps with that of CeD itself.…”
Section: Patient Follow-upmentioning
confidence: 99%
“…Diagnosis of CD in adults is based on villous atrophy and positive celiac-specific serology, including tissue transglutaminase and endomysial antibodies [1][2][3][4]. Although a strict lifelong gluten-free diet (GFD) is the mainstay for the treatment of CD, leading to the resolution of clinical symptoms and histological lesions in the vast majority of patients, [1][2][3]5] persistence of gastrointestinal symptoms despite a GFD is a relevant clinical scenario, occurring in up to 30-40% of coeliac patients [6][7][8][9][10][11][12]. Ongoing symptoms in treated coeliac patients are associated with a significant social and psychological burden, leading to a reduced quality of life (QOL) and increased healthcare expenditure [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Poor adherence to a GFD, either voluntarily or inadvertently, is a major cause of ongoing symptoms in coeliac patients [6][7][8][9][10][11][12], and, although rare, life-threatening conditions, such as refrac-tory CD, lymphoma and other malignant complications of CD should be excluded [6,[8][9][10]14,15]. Apart from these aetiologies, it has been shown that up to 50% of coeliac patients may experience ongoing chronic functional gastrointestinal symptoms that are compatible with functional gastrointestinal disorders (FGID) despite being on a GFD [6,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%